2019
DOI: 10.3390/mi10100657
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Rarefaction and Effective Viscosity on Micro-Elasto-Aerodynamic Lubrication Performance of Gas Microbearings

Abstract: Elastic deformation and gaseous rarefaction effects are of great importance to the static and dynamic characteristics of gas microbearings. Based on the effective viscosity model of Veijola, the governing equations can be solved by the partial derivative method, finite element procedure, and relaxed iterative algorithm. The numerical results showed that the maximum gas pressure is relatively lower compared to a microbearing with a rigid liner at a local pressure peak region, owing to the film thickness of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…After the static pressure and gas film thickness are obtained, according to the small perturbation method based on the linearization hypothesis, the time-dependent modified Reynolds Equation (1) for ultra-thin gas lubrication of a journal microbearing is solved by the partial derivative method [40,41], and the dynamic coefficients K ij and D ij (i, j = x, y) that depend on the excitation frequency are computed. The detailed solution process is given in reference [42].…”
Section: Methodsmentioning
confidence: 99%
“…After the static pressure and gas film thickness are obtained, according to the small perturbation method based on the linearization hypothesis, the time-dependent modified Reynolds Equation (1) for ultra-thin gas lubrication of a journal microbearing is solved by the partial derivative method [40,41], and the dynamic coefficients K ij and D ij (i, j = x, y) that depend on the excitation frequency are computed. The detailed solution process is given in reference [42].…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [ 22 ] explored the mechanism of synergetic lubrication by both experiment and CFD, and emphasized the significant influence of lubricant viscosity. Other scholars also pay attention to the investigation of journal bearings [ 23 , 24 , 25 , 26 ]. Li et al [ 23 ] investigated the microbearings and found that the rise of temperature would weaken the load capacity and negatively influence the operating stability of microbearings.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 23 ] investigated the microbearings and found that the rise of temperature would weaken the load capacity and negatively influence the operating stability of microbearings. Wu et al [ 24 ] studied the static and dynamic characteristics of gas bearings based on viscosity model of Veijola and declaimed that the effective viscosity of the lubricant would lead to a decreased load carrying capacity. Besides, Chen et al [ 25 ] focused on the fabrication of a biomimetic superhydrophobic surface in the application of a water-lubricated bearing, which enlarged the research scope of surface lubrication of bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Its structure size is very small, the lubricating film is very thin, and the lubricating gas has a certain thinning effect [8]. Then, at low speed, the contact friction state between the flat foil and the rotor surface slowly transits to the gas dynamic pressure lubrication state, the lubrication film thickness increases from zero, and the influence of gas rarefaction will be more obvious [9]. Therefore, it is necessary to consider the effect of gas rarefaction in the related research, which is of great significance to accurately predict the performance of foil bearing and accurately design the structure of foil bearing.…”
Section: Introductionmentioning
confidence: 99%